Global Trend of Breast Cancer Mortality Rate: A 25-Year Study - Azamjah, Nasrindokht; Soltan-Zadeh, Yasaman; Zayeri, Farid (Asian Pacific journal of cancer prevention : APJCP, 2019)
Background: breast cancer is the most common cause of cancer death for women worldwide. In the past two decades, published epidemiological reports in different parts of the world show significant increase in breast cancer mortality rate. The aim of this study was to determine the 25-year trend of breast cancer mortality rate in 7 super regions defined by the Health Metrics and Evaluation (IHME), i.e. Sub-Saharan Africa, North Africa and Middle East, South Asia, Southeast Asia and East Asia and Oceania, Latin America and Caribbean, Central Europe and Eastern Europe and Central Asia, High-income. Methods: Our study population consisted of 195 world countries in the IHME pre-defined seven super regions. The age-standardized mortality rates from 1990 to 2015 were extracted from the IHME site. The reference life table for calculating mortality rates was constructed based on the lowest estimated age-specific mortality rates from all locations with populations over 5 million in the 2015 iteration of GBD. To determine the trend of breast cancer mortality rate, a generalized linear mixed model was fitted separately for each IHME region and super region. Results: Statistical analysis showed a significant increase for breast cancer mortality rate in all super regions, except for High-income super region. For total world countries, the mean breast cancer mortality rate was 13.77 per 100,000 in 1990 and the overall slope of mortality rate was 0.7 per 100,000 from 1990 to 2015. The results showed that Latin America and Caribbean the highest increasing trend of breast cancer mortality rate during the years 1990 to 2015 (1.48 per 100,000). Conclusion: In general, our finding showed a significant increase in breast cancer mortality rate in the world during the past 25 years, which could be due to increase in incidence and prevalence of this cancer. Low this increasing trend is an alarm for health policy makers in all countries, especially in developing countries and low-income regions which experienced sharp slopes of breast cancer mortality rate.